2021
DOI: 10.3390/ijerph18157828
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of the “FUNPALs Playgroup” Intervention to Improve Toddler Dietary and Activity Behaviors: A Pilot Randomized Controlled Trial

Abstract: This study evaluated the feasibility and effects of the Families Understanding Nutrition and Physically Active Lifestyles (FUNPALs) Playgroup on toddler (12–36-month-old) diet and activity behaviors. Parent–toddler dyads were recruited from disadvantaged communities and randomly assigned to receive 10-weekly sessions of the FUNPALs Playgroup (n = 24) or dose-matched health education control group (n = 26). FUNPALs Playgroups involved physical and snack activities, delivery of health information, and positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The Abriendo Caminos intervention significantly decreased SSBs intake among children in the intervention arm. Changes in SSBs consumption are consistent with findings from other studies that aimed to decrease intake in Hispanic children [ 10 , 42 , 43 , 44 ]. A nine-month intervention aimed to improve dietary behaviors in young Hispanic children observed a decrease in SSBs consumption and increased water and milk intake [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…The Abriendo Caminos intervention significantly decreased SSBs intake among children in the intervention arm. Changes in SSBs consumption are consistent with findings from other studies that aimed to decrease intake in Hispanic children [ 10 , 42 , 43 , 44 ]. A nine-month intervention aimed to improve dietary behaviors in young Hispanic children observed a decrease in SSBs consumption and increased water and milk intake [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…The primary analysis found that sleep interventions were associated with 10.5 minutes (95% CI, 5.6-15.4; P < .001) longer nocturnal sleep duration compared with the control condition. Figure 2 shows the primary meta-analysis forest plot, with quality assessments . There was marked heterogeneity across study estimates ( I 2 = 87.2%).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, obesogenic food availability was negatively associated with parental feeding practices. Two early childhood studies present feasibility and efficacy results from the FUNPALS Playgroup and the Prevention of Overweight in Infancy randomised control trials ( 16 , 17 ) ; however, no significant differences or associations were found for home food availability. Although healthy and unhealthy food availability may indicate some aspects of a child’s diet, there is limited evidence that home food availability influences desired outcomes or improves because of an intervention.…”
mentioning
confidence: 98%
“…First, although the HFI scores were generally associated with food and nutrient intake, Fulkerson and colleagues (13) only examined five out of thirteen major category scores from the HFI and compared the five scores against a limited number of food and nutrient intake indicators. Second, despite its use with early childhood samples (15)(16)(17)(18)(19) , the HFI was validated using a sample of 10-17-year-old children, who have different energy and nutrient needs than their younger counterparts. Relatedly, most of the early childhood research has largely relied on cross-sectional designs, limiting our understanding of changes in home food availability over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation